SOSIALISASI PENTINGNYA KOMUNIKASI ANTAR PETUGAS KESEHATAN AGAR TERCAPAINYA KOMUNIKASI EFEKTIF DI RUMAH SAKIT UMUM DELIA KABUPATEN LANGKAT (Poltekkes Kemenkes Bandung, 2023)
Improving the quality of service is a top priority in all hospitals. These efforts are carried out through the construction of facilities, infrastructure, procurement of equipment and manpower and other software, in line with the construction of hospitals in general. However, it is also realized that there are still many obstacles to be faced, especially those related to standard needs and demands for service systems that are still not in line with the rapid development of medical science and technology where specialist and sub-specialist services tend to develop. With the increasing demands of the community for the quality of these services, the function of health services, including services in hospitals, needs to be continuously improved in stages so that they become more effective and efficient and give satisfaction to patients, families and the community. Patient Safety is a system where hospitals make patient care safer, including risk assessment, identification and management of patient risks, reporting and analysis of incidents, the ability to learn from incidents and their follow-up, and implementation of solutions to minimize risks and prevent injuries caused. by mistake as a result of carrying out an action or not taking the action that should be taken. The approach method used is lectures and questions and answers / information / education, discussion and technical guidance. Through this community service activity, the participants, especially those related to PMKP (Quality Improvement and Patient Safety) understand more about the importance, especially when there are Hospital accreditation activities because many do not understand PMPK. There is additional knowledge about this PMKP so that when PMKP accreditation is carried out it becomes the center of attention because it has been carried out properly and correctly.